PKM BIMBINGAN KONSELING ISLAM PADA PASIEN RAWAT INAP DI RUMAH SAKIT PROVINSI JAMBI - Kusnadi, Edy; Munsarida, Munsarida; Suprihatin, Suprihatin (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Islamic guidance and counseling is a very important thing to do in the hospital, this is a form of attention that is really needed by inpatients. As for the response of the patient, the patient's family and the hospital staff to the implementation of Islamic guidance and counseling was very well received. For this reason, hospital management can pay more attention to the role of Islamic guidance and counseling which is also very helpful in healing to provide peace of mind for inpatients